3 hours a day : how entrepreneurs can multiply their income by working less and living more - Williams, Knolly (McGraw Hill-Ascent Audio, 2023)
It wasn't long ago that entrepreneurs believed non-stop hustle was essential for success, equating the hours put in to their level of ambition. But for many independent business owners today, living through the stressful pandemic years has shown there has to be a better, more sustainable way. In 3 Hours a Day, Knolly Williams offers first-hand evidence that smart entrepreneurs can do what they love-and enjoy far more money and free time-while working less and living more. Williams, also known as The Business Healer, shows you how to transform your work life in a proven 7-step process that includes prioritizing dollar-producing activities while relegating non-dollar producing activities to your capable crew. In this book, you'll learn how to: hone your superpower, evaluate your business, balance your business, delegate your business, organize your business, design your 3-hour workday, and quadruple your sales. Filled with practical advice, useful tips for prioritizing, and more, the blueprint offered in 3 Hours a Day gives you the freedom you've been striving for-financial freedom, time freedom, and location freedom-and the life that comes along with it.